The influence of time feed restriction on efficiency of protein utilization in growing period of broiler chicken - Berliana, Berliana; Aziz, Abdul (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2016)
The research aim was to determine the influence of time feed restriction on the efficiency of protein utilization in growing period of broiler. Materials used in this experiment were 500 22 - 42-day-old broilers. The commercial pelleted feed containing 19% protein and 3100 kcal/kg of ME for grower period was used. The treatments were P0 (feed was provided ad libitum from 7 to 42 day of age, P1 (feed was provided ad libitum from 22 to 42 day of age), P2 (feed was provided 8 hours a day, with time composition 3 hr in the morning (08.00-11.00) and 5 hr in the afternoon till night (16.00-21.00)), P3 (feed was provided 10 hours a day, with time composition 3 hr in the morning (08.00-11.00) and 7 hr in the afternoon till night (16.00-23.00)) dan P4 (feed was provided 12 hours a day, with time composition 3 hr in the morning (08.00-11.00) and 9 hr in the afternoon till night (16.00-01.00)). Completely Randomized Design with 5 treatments and 4 replicationS was used in this experiment. Parameters measured were feed intake, protein consumption, body weight gain and efficiency of protein utilization. The result showed that time length to provide the feed was significantly reduced (P<0.05) feed intake, protein consumption and was significantly increased (P<0.05) the efficiency of protein utilization. Therefore, body weight was the same for all treatments. It concluded that 8 hours a day for time length to proved the feed could increase the efficiency of protein utilization and did not interfere body weight gain.